A randomized comparative trial of early initiation of oral maternal feeding versus conventional oral feeding after cesarean delivery. Issue 2 (29th April 2014) - Masood, Shabeen N.; Masood, Yasir; Naim, Uzma; Masood, Muhammad F.
Abstract: Objective: To compare the effects of two maternal feeding policies—early versus conventional oral feeding—after cesarean delivery. Methods: This prospective multicenter randomized comparative trial was conducted at tertiary care hospitals in Sindh, Pakistan, from 2010 to 2012. Women with an uncomplicated cesarean delivery under spinal anesthesia were allocated to an intervention of early (after 2 hours) or conventional (after 18 hours) initiation of oral feeding. Outcomes included maternal ambulation, maternal satisfaction, gastrointestinal functions, and length of hospital stay. Results: In total, 1174 women (n = 587 per group) were included in the final analysis. Gastrointestinal complications were not significantly different between the two groups. Lower intensities of thirst and hunger and a higher rate of maternal satisfaction were observed in the early feeding group ( P < 0.05), and 53.8% of women in this group were able to ambulate within 15 hours of surgery, compared with 27.9% of women in the conventional feeding group. The frequencies of readmission, febrile morbidity, and wound infection were insignificant. Conclusion: Early oral dietary initiation after cesarean delivery resulted in early ambulation, greater maternal satisfaction, and reduced length of hospital stay, with no detrimental outcomes, making this practice cost‐effective. Hence, day‐care cesarean delivery might be an option in resource‐constrained settings. Trial Registration number: ChiCTR‐TRC‐13003651, http://www.chictr.org